ANALYSIS OF ENGLISH LEARNING STRATEGIES USED BY THE DEAF STUDENTS IN SLB-B KARYA MULIA SURABAYA : A CASE STUDY - ISKANDAR, ISMI BERLIANTIKA (Jurnal Ilmiah Mahasiswa FIB, 2014)
Iskandar, Ismi Berliantika. 2014. Analysis of English Learning Strategies Used by the Deaf Student in  SLB-B Karya Mulia Surabaya: a Case Study.  Study Program of English, Department of Language and Literature, Faculty of Cultural Studies, Universitas Brawijaya. Supervisor: Endang Sasanti; Co-supervisor: Emy SudarwatiKeyword: Language Learning Strategies, DeafEnglish is the most widely used language for International communication that has been recognized worldwide. So now in Indonesia, English is  given to almost all students, including students with special needs  is also commonly called disables. However, the deaf students still have difficulty in applying English. This occurs because English is a foreign language in Indonesia. Another cause of difficulty in learning English is about students’ habit. Facing that phenomena, the language learning strategies are needed. This study only  focuses on the learning strategies performed by the deaf student when learning English. The approach used is qualitative study. This study was a case study. The respondents of this study were two students, male and female.  The  writer conducted the interview with the respondents and teacher. The writer collected the data by selecting deaf student attending class 2, recording  and conducting interviews, identifying the learning strategies used by the student, and classifying the learning strategies used by the student. The data analysis was conducted by analyzing the results of the interview, comparing the results of interview with students' English grades for learning  and drawing conclusion based on the problems of study and the result of data analysis. The result of this study shows that memory strategies are the most strategy used  by respondents whereas affective strategies are the  least strategy  used.  In addition to using these strategies, the support from teachers  and parents  is very important to help them learn a new language. The writer suggests for the students to  combine  learning strategies with each other. The writer also suggests the teacher to add other teaching  innovations that  can  help  students  learning  English lessons. The last suggestion  is  for the future researchers to do a closer and spacious study with deaf students.